Assessing the EKC hypothesis by considering the supply chain disruption and greener energy: findings in the lens of sustainable development goals - Mohammed, Kamel Si; Tiwari, Sunil; Ferraz, Diogo [UNESP]; Shahzadi, Irum [UNESP] (Springer Nature, 2023)
This paper investigates the effect of the supply chain disruption, greener energy consumption, and economic growth on carbon emissions in advanced economies and emerging markets from 1997 to 2021 using panel quantile autoregressive distributed lags (QARDL) and the panel quantile regression (QR). The results of the two models confirm, on the one hand, the validity of the environmental Kuznets curve (EKC) hypothesis and, on the other hand, the role of renewable energy consumption in mitigating carbon emissions in advanced and developing economies. Furthermore, the finding shows that the supply chain disruption for the long run is positive at all quantiles, indicating the evidence of association at the extreme low and high quantiles than at the intermediate quantile. In addition, the effect of the supply chain decreases at the lower quantile. It turns negative at the upper 90th quantile in the short run, indicating that the supply chain disruption reduces the environmental degradation under the bearish market conditions. In the future, the increasing supply chain disruptions due to the Russia-Ukraine conflict and further COVID-19 worldwide can consider sluggish economic growth and play an essential role in promoting renewable energy abundance and reducing CO2 emissions. Practical implications are reported in the lens of carbon neutrality and structural changes.
Keywords: Carbon emissions; Greener energy; Panel quantile ARDL; Supply chain disruption